Demonstration of synergistic catalysis in Au@Ni bimetallic core-shell nanostructures - Vysakh, A. B.; Babu, Chinchu Lizen; Vinod, C. P. (Journal of Physical Chemistry C, 2015)
Coreshell bimetallic nanoparticles comprised of gold core and varying nickel shell have been synthesized, and their synergistic effect in catalysis is explored through catalytic hydrogenation of p-nitrophenol and p-nitrothiophenol. A clear evidence for synergism in Au@Ni core-shell nanoparticles having an ultrathin Ni shell (1-2 nm) around a Au core (6-10 nm) resulting in enhanced catalytic activity is observed. The rates observed from a thin nickel shell are higher than monometallic Au or Ni nanoparticles of similar size or with a thicker Ni shell of 6-8 nm.

Phenylacetylene hydrogenation on Au@Ni bimetallic core-shell nanoparticles synthesized under mild conditions - Vysakh, A. B.; Lazar, Anish; Yadukiran, V.; Singh, A. P.; Vinod, C. P. (Catalysis Science & Technology, 2016)
The synthesis of Au@Ni bimetallic core-shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy is reported. The method is found to be useful for the synthesis of a very thin nickel shell (2 nm) over a gold core (15 nm). Synergistic effects are observed in catalyzing phenylacetylene hydrogenation under different solvent conditions.

Model nanoparticles in catalysis - Vinod, C. P.; Vysakh, A. B.; Sreedhala, S. (Metal nanoparticles and clusters: advances in synthesis, properties and applications, 2017)
The importance of surface structure in catalysis is well documented by a large volume of surface science studies carried out on single crystal surfaces. Recent years has seen rapid strides in the synthesis of structured nanomaterials with varying morphologies and architecture. There is a growing interest in utilizing model nanoparticles like morphology-controlled nanostructures and core–shell-like bimetallic nanoparticles in catalysis. Apart from showing unprecedented reactivity, they serve as a model surfaces to answer many fundamental question in catalysis and also to arrive at structure vs activity correlations in heterogeneous catalysis. This chapter gives an introduction to such nanomaterials and recent advances in utilizing these materials for catalytic applications.

Surfactant free synthesis of Au@Ni core-shell nanochains in aqueous medium as efficient transfer hydrogenation catalyst - Vysakh, A. B.; Shebin, K. J.; Jain, Ruchi; Sumanta, P.; Gopinath, Chinnakonda S.; Vinod, C. P. (Applied Catalysis A-General, 2019)
A surfactant free aqueous phase synthesis method is reported for the generation of highly lattice mismatched Au@Ni core-shell nanochains without using any expensive and hazardous organic ligands. As synthesised Au@Ni nanochain structures showed high thermal stability and bulk oxidation resistance up to 300 degrees C. In situ near ambient pressure XPS (NAPXPS) analysis has been done for the bare Au@Ni nanochain surfaces under oxygen atmosphere and at different temperatures which showed evidence for the surface oxidation resistance of naked Au@Ni nanochains up to 200 degrees C. Ligand or capping agent free Au@Ni nanochain surfaces are found to be highly active for transfer hydrogenation of acetophenone to 1-phenyl ethanol an important commodity in perfumery industry.
Keywords: Au@Ni nanochains; core-shell; NAPXPS; Surfactant free; synergistic effects; transfer hydrogenation